Transnational Bodies in Transit : New Routes for Affective Transpositions in Shani Mootoo’s Polar Vortex - Llarena Ascanio, María Jesús (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article puts Shani Mootoo’s novel, Polar Vortex (2020), in conversation with the vitalist philosophy of Rosi Braidotti, as illustrated in the study Posthuman Feminism (2022) and Libe García Zarranz “Sustainable Affects” (2017a, 2020b). I look at the centrality of affective relations in the transformation of queer subjectivity under processes of the growing (un)happiness in the diasporic homeSpace. Shani Mootoo’s (non)diasporic cross-border narrative proposes contrastive figurations of the subject through temporal and spatial frameworks. Mootoo’s “transposable moves” resist a naïve return to sentimentality or nostalgic love to advocate instead a turn to sustainable affects.